2023
DOI: 10.3390/ijms241411680
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Biofilm Formation on Biomaterials and Approaches to Its Treatment and Prevention

Abstract: Bacterial biofilms can cause widespread infection. In addition to causing urinary tract infections and pulmonary infections in patients with cystic fibrosis, biofilms can help microorganisms adhere to the surfaces of various medical devices, causing biofilm-associated infections on the surfaces of biomaterials such as venous ducts, joint prostheses, mechanical heart valves, and catheters. Biofilms provide a protective barrier for bacteria and provide resistance to antimicrobial agents, which increases the morb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 201 publications
(230 reference statements)
1
34
0
Order By: Relevance
“…epidermidis were similar to an existing report and the minimum concentration of MGO required to kill both bacteria was estimated as 9 mM. It is well-known from the literature that when implantation occurs in the body, early-stage infections can occur, and treating them with antibiotics is difficult if they persist in forming biofilms. , In our work, we explored two strategies: (i) the release of MGO for the prevention of bacteria and (ii) the contact-killing of bacteria. Therefore, we have included MGO in the top layers (L5―1×, L7―2×, and L9―3×) to enhance the bacterial killing efficacy of the HA/J-Coll LbL coating through the release of MGO and contact-killing.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…epidermidis were similar to an existing report and the minimum concentration of MGO required to kill both bacteria was estimated as 9 mM. It is well-known from the literature that when implantation occurs in the body, early-stage infections can occur, and treating them with antibiotics is difficult if they persist in forming biofilms. , In our work, we explored two strategies: (i) the release of MGO for the prevention of bacteria and (ii) the contact-killing of bacteria. Therefore, we have included MGO in the top layers (L5―1×, L7―2×, and L9―3×) to enhance the bacterial killing efficacy of the HA/J-Coll LbL coating through the release of MGO and contact-killing.…”
Section: Discussionsupporting
confidence: 74%
“…It is well-known from the literature that when implantation occurs in the body, early-stage infections can occur, and treating them with antibiotics is difficult if they persist in forming biofilms. 39,40 In our work, we explored two strategies: (i) the release of MGO for the prevention of bacteria and (ii) the contact-killing of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The implications of the findings reported here are significant in the study of prevention and control of biofilm disease. Strategies to combat biofilm growth include antibiofilm coatings to repel bacteria with bactericidal, topographical, chemical, or electrostatic interactions. Indeed, one study revealed that modifying surfaces with immobilized DNA leads to reduced bacterial attachment, potentially due to electrostatic repulsion between the negative charges of DNA and bacterial cell surfaces . The clinical implementation of DNA-coated surfaces may necessarily rely on an understanding of ionic interactions at the biofilm–substrate interface.…”
Section: Resultsmentioning
confidence: 99%
“…Bacterial infection is one of the most common medical complications caused by biomaterials being inserted into or coming into contact with the body. 1 Ventilator-associated pneumonia (VAP) is a hospital-acquired respiratory infection that commonly occurs in patients who receive mechanical ventilation via the endotracheal tube (ETT). 2 It happens because bacteria rapidly form colonies on the surface of the ETT, become permanently attached, produce extracellular polysaccharides, and develop a microbial biofilm.…”
Section: Introductionmentioning
confidence: 99%